Dynamic Response of Linear Mechanical Systems Modeling, Analysis and Simulation - Angeles, Jorge; SpringerLink (Online service) (Boston, MA : Springer US : Imprint: Springer, 2012)
Dynamic Response of Linear Mechanical Systems: Modeling, Analysis and Simulation can be utilized for a variety of courses, including junior and senior-level vibration and linear mechanical analysis courses. The author connects, by means of a rigorous, yet intuitive approach, the theory of vibration with the more general theory of systems. The book features: A seven-step modeling technique that helps structure the rather unstructured process of mechanical-system modeling A system-theoretic approach to deriving the time response of the linear mathematical models of mechanical systems The modal analysis and the time response of two-degree-of-freedom systems$1 (Bthe first step on the long way to the more elaborate study of multi-degree-of-freedom systems$1 (Busing the Mohr circle Simple, yet powerful simulation algorithms that exploit the linearity of the system for both single- and multi-degree-of-freedom systems Examples and exercises that rely on modern computational toolboxes for both numerical and symbolic computations as well as a Solutions Manual for instructors, with complete solutions of a sample of end-of-chapter exercises Chapters 3 and 7, on simulation, include in each (3z(BExercises(3y (Bsection a set of miniprojects that require code-writing to implement the algorithms developed in these chapterss
1. The Modeling of Single-DOF Mechanical Systems -- 2. Time Response of First- and Second-Order Dynamical Systems -- 3. Simulation of Single-DOF Systems -- 4. Modeling of Multi-DOF Mechanical Systems -- 5. Vibration Analysis of Two-DOF Systems -- 6. Vibration Analysis of n-DOF Systems -- 7. Simulation of n-DOF Systems -- 8. Vibration Analysis of Continuous Systems.
Keywords: Engineering; Mechanical engineering; Engineering; Control, Robotics, Mechatronics; Mechanical Engineering